Fresh Properties of Lightweight Concrete and Lightweight Self Compacting Concrete Produced with Pumice Aggregate - Baban Jamal Hamasalh; Bahman Omar Taha; Ganjeena Jalal Khoshnaw (Eurasian Journal of Science and Engineering, 2020)
Lightweight aggregates have long been used widely in construction worldwide. One of the most widely used lightweight aggregate in concrete construction is Pumice. This paper investigates the lightweight concrete (LWC) and lightweight self-compacting concrete’s (LWSCC) fresh properties produced by using pumice aggregates. Two groups of concrete were made, first lightweight concrete, and the second group was lightweight self-compacting concrete by using lightweight coarse and fine aggregate (Pumice) (50% – 60% by volume) with fine natural aggregates (50% – 40% by volume). 10% of silica fume was used as cement replacement with a constant (0.40) water-to-binder ratio by mass. Both groups of concrete’s rheological properties were studied by conducting a comprehensive series test (slump, slump flow, J–Ring, L-Box, and V-Funnel). The fresh densities and workability tests showed that this lightweight concrete meets the lightweight structural concrete requirements. Developing LWC and LWSCC with acceptable rheological characteristics and density, which are more environmentally friendly, and low-cost, will support the sustainable construction and reconstruction of volcanic disaster regions worldwide.